Diversification of refugia types needed to secure the future of coral reefs subject to climate change - McClanahan, Tim R.; Darling, Emily S.; Beger, Maria; Fox, Helen E.; Grantham, Hedley S.; Jupiter, Stacy D.; Logan, Cheryl A.; Mcleod, Elizabeth; McManus, Lisa C.; Oddenyo, Remy M.; Surya, Gautam S.; Wenger, Amelia. S.; et al. (Conservation biology, 2024)
Identifying locations of refugia from the thermal stresses of climate change for coral reefs and better managing them is one of the key recommendations for climate change adaptation. We review and summarize approximately 30 years of applied research focused on identifying climate refugia to prioritize the conservation actions for coral reefs under rapid climate change. We found that currently proposed climate refugia and the locations predicted to avoid future coral losses are highly reliant on  excess heat metrics, such as degree heating weeks. However, many existing alternative environmental, ecological, and life‐history variables could be used to identify other types of refugia that lead to the desired diversified portfolio for coral reef conservation. To improve conservation priorities for coral reefs, there is a need to evaluate and validate the predictions of climate refugia with long‐term field data on coral abundance, diversity, and functioning. There is also the need to identify and safeguard locations displaying resistance toprolonged exposure to heat waves and the ability to recover quickly after thermal exposure. We recommend using more metrics to identify a portfolio of potential refugia sites for coral reefs that can avoid, resist, and recover from exposure to high ocean temperatures and the consequences of climate change, thereby shifting past efforts focused on avoidance to a diversified risk‐spreading portfolio that can be used to improve strategic coral reef conservation in a rapidly warming climate. Diversificación de los tipos de refugio necesarios para asegurar el futuro de los arrecifes de coral sujetos al cambio climático Resumen Una de las principales recomendaciones para la adaptación al cambio climático es identificar los refugios de los arrecifes de coral frente al estrés térmico del cambio climático y mejorar su gestión. Revisamos y resumimos ∼30 años de investigación aplicada centrada en la identificación de refugios climáticos para priorizar las acciones de conservación de los arrecifes de coral bajo un rápido cambio climático. Descubrimos que los refugios climáticos propuestos actualmente y las ubicaciones que pueden evitarlos dependen en gran medida de métricas de exceso de calor, como las semanas de calentamiento en grados (SCG). Sin embargo, existen muchas variables alternativas de historia vital, ambientales y ecológicas que podrían utilizarse para identificar otros tipos de refugios que resulten en el acervo diversificado que se desea para la conservación de los arrecifes de coral. Para mejorar las prioridades de conservación de los arrecifes de coral, es necesario evaluar y validar las predicciones sobre refugios climáticos con datos de campo a largo plazo sobre abundancia, diversidad y funcionamiento de los corales. También es necesario identificar y salvaguardar lugares que muestren resistencia a la exposición climática prolongada a olas de calor y la capacidad de recuperarse rápidamente tras la exposición térmica. Recomendamos utilizar más métricas para identificar un acervo de posibles lugares de refugio para los arrecifes de coral que puedan evitar, resistir y recuperarse de la exposición a las altas temperaturas oceánicas y las consecuencias del cambio climático, para así desplazar los esfuerzos pasados centrados en la evitación hacia un acervo diversificado de riesgos que pueda utilizarse para mejorar la conservación estratégica de los arrecifes de coral en un clima que se calienta rápidamente. 需要多样化的避难所来保障受气候变化影响的珊瑚礁的未来 【摘要】识别保护珊瑚礁免受气候变化热胁迫影响的避难所并加强其管理是气候变化适应的重要建议之一。我们回顾和总结了约30年来关注如何确定气候避难所来优先保护受快速气候变化影响的珊瑚礁的应用研究。我们发现, 目前提出的气候避难所及可以避开气候变化影响的地点高度依赖于衡量过多热量的指标, 如周热度。然而, 还存在许多替代性的环境、生态和生活史变量, 可用于确定其他类型的避难所, 它们可以提供珊瑚礁保护所需的多样化组合。为了改进珊瑚礁的优先保护决策, 需要用珊瑚丰度、多样性和功能的长期野外数据来评估和验证对气候避难所的预测。还需要识别和保护表现出气候抵抗力的地点, 即长期暴露在热浪中且在热暴露后能够迅速恢复的地点。我们建议使用更多指标, 为珊瑚礁确定潜在的避难所组合, 帮助珊瑚礁避免和抵抗海洋高温暴露和气候变化的影响, 并得到更好的恢复, 从而将过去专注于避免海洋高温暴露的努力转变为多样化的风险分散组合, 来促进快速气候变暖下的珊瑚礁战略保护。【翻译:胡怡思;审校:聂永刚】